Isolation and bioactivities of constitutents of the roots of Garcinia atroviridis - Permana, Dharma; Lajis, Nordin; Mackeen, Mukram M.; Ali, Abdul M.; Aimi, Norio; Kitajima, Mariko; Takayama, Hiromitsu (American Chemical Society, 2001)
Two new prenylated compounds, the benzoquinone atrovirinone (1) and the depsidone atrovirisidone (2), were isolated from the roots of Garcinia atroviridis. Their structures were determined on the basis of the analysis of spectroscopic data. While compound 2 showed some cytotoxicity against HeLa cells, both compounds 1 and 2 were only mildly inhibitory toward Bacillus cereus and Staphylococcus aureus.